Diagnosis Komunitas dalam Upaya Penurunan Kasus Stunting di Desa Sukaharja, Wilayah Kerja Puskesmas Sindang Jaya - Barii Ikraam Majiid Ahmad; Zita Atzmardina (Malahayati Nursing Journal, 2025)
ABSTRACT Stunting is a serious health problem that affects the growth and development of children, especially in areas with limited access to balanced nutrition. This study aims to conduct a community diagnosis to reduce stunting cases in Sukaharja Village, the working area of Sindang Jaya Community Health Centre, Tangerang District, Banten Province. Through a qualitative approach, this study identified locations with increasing cases of stunting and the problems that cause it. Two interventions were conducted: counselling on stunting and prevention efforts using the ‘ABCDE’ method, and training on how to prepare a balanced nutrition menu. The results of the interventions showed an increase in participants' knowledge, with 88.9% having an increase in post-test scores and 97.22% scoring above 70. In addition, 36 demonstration participants successfully performed the practices. These findings emphasise the importance of community-based approaches in increasing community awareness and knowledge on stunting prevention, as well as the need for effective nutrition interventions to support optimal child growth. Keywords: Stunting, Balanced Nutrition, Community Diagnosis   ABSTRAK Stunting ialah sebuah masalah kesehatan serius yang memiliki dampak pada tumbuh dan kembangnya anak, khusunya di daerah dengan akses terbatas terhadap gizi seimbang. Kegiatan ini bertujuan untuk melakukan diagnosis komunitas guna menurunkan kasus stunting di Desa Sukaharja, wilayah kerja Puskesmas Sindang Jaya, Kabupaten Tangerang, Provinsi Banten. Melalui pendekatan kualitatif, kegiatan ini mengidentifikasi lokasi dengan peningkatan kasus stunting dan masalah-masalah yang menyebabkannya. Dua intervensi dilakukan: penyuluhan mengenai stunting dan upaya pencegahan dengan metode “ABCDE,” serta pelatihan penyusunan menu gizi seimbang. Hasil intervensi menunjukkan peningkatan pengetahuan peserta, di mana 88,9% mengalami kenaikan nilai post-test dan 97,22% memperoleh nilai di atas 70. Selain itu, 36 peserta demonstrasi berhasil melakukan praktik dengan baik. Temuan ini menegaskan pentingnya pendekatan berbasis komunitas dalam peningkatan kesadaran serta wawasan masyarakat mengenai pencegahan stunting, serta kebutuhan akan intervensi gizi yang efektif untuk mendukung pertumbuhan anak yang optimal.  Kata Kunci: Stunting, Gizi Seimbang, Diagnosis Komunitas